Child maltreatment and adjustment to confinement: an exploratory study of male juvenile offenders in China - Zhao, Ruohui (Journal of family violence, 2021)
Whereas Western research has shown that childhood maltreatment experiences may have a negative impact on inmates’ adjustment to confinement, such studies are rare in China. The present study aims to address the respective research gap. In a two-wave longitudinal project, 514 male juvenile offenders were interviewed in a centralized provincial juvenile reformatory in southwest China regarding their childhood maltreatment experiences, incarceration experiences, and their pre-incarceration at-risk behaviors or experiences. While controlling for demographic characteristics and variables derived from correctional importation and deprivation models, multiple linear regression analyses show a significant correlation between childhood maltreatment experiences and juveniles’ adjustment to confinement. Specifically, there is a positive correlation between the level of childhood emotional abuse and negative emotions among incarcerated juveniles, a negative correlation between childhood emotional neglect and juvenile offenders’ adjustment to prison life, and a positive correlation between childhood sexual abuse experiences and adjustment to prison life. The present study provides evidence that child maltreatment, especially emotional abuse and neglect, impacts juvenile offenders’ adjustment to confinement in China. This demonstrates the importance of offering institutional programs that would assist juvenile offenders with childhood maltreatment experiences, especially those of emotional abuse or neglect. Tentative explanations are provided for unexpected findings.